Istiratijiyatu Ta'lim al-Lughah al-'Arabiyyah 'Abra Wasail al-Tawasul al-Ijtima'i al-Iliktruni: Dirasah Halah fi Markaz al-'Arabiyyah Pare Kediri - Firdaus, Rousul; Mabrurrosi, Mabrurrosi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This research departs from the rise of the phenomenon of online learning that has occurred recently, both in formal and non-formal schools. The objectives of this study include: first, to find strategies used in learning Arabic through social media at Markaz Arabiyah Pare Kediri. Second, the supporting and inhibiting factors in learning Arabic through social media at the Pare Kediri Arabiyah Markaz. Third, to find advantages and disadvantages in learning Arabic through social media at the Pare Kediri Arabiyah Markaz. This study uses a qualitative research design with a case study type. The data collection techniques are carried out through observation, interviews and documentation. To analyze the data, the researcher uses the theory of analysis according to Miles and Hiberman by collecting data, presenting data, reducing data, and drawing conclusions. At the stage of checking the validity of the data, researchers used the triangulation method. The results of the study show that (a) the strategies used in learning Arabic through social media include student-centered strategies, teaching material-centered strategies, heuristics, direct instruction strategies, interactive learning strategies and independent learning strategies. (b) supporting factors consist of intrinsic factors such as student motivation and discipline. Extrinsic such as, availability of internet quota, strong network, supportive environment, intensive supervision, attractive methods and strategies that are relevant and effective. The obstacles faced by the majority are the limited quota they have, the weak network, the lack of student motivation and the difficulty of supervising them. (c) the advantages and disadvantages consist of 3 things, namely: first the advantages and disadvantages of aspects of the learning process such as interactive, direct service from the teacher, conditional time, while the drawback is that it is less effective when compared to offline classes and others. Second, the advantages and disadvantages of the aspects of the device used are more flexible, not limited by space, while the disadvantages are blurry cameras, limited cellphone specifications and others. Third, the advantages and disadvantages of aspects of the application used, such as the application being easy to use, while the disadvantages are extravagant quota, requiring a strong signal.